Kulturne pogojenosti poučevanja poljščine kot tujega jezika - Tambor, Jolanta (Jezik in slovstvo, 2017)
Horizontal division of the learning/teaching process is often mentioned in contemporary definitions and glottodidactic descriptions. This practical approach allows one to determine the criteria necessary for appropriate, homogeneous and consistent evaluation of the results of teaching and the level of language proficiency (Seretny, Lipińska 2005). However, this process should also be regarded as vertically diversified: the degree of involvement in evaluation and cognitive competence in each skill. In the case of a learned or acquired language, the level of proficiency can be described as close to that of a native speaker only when a speaker can derive meaning from the context and can modify the meaning because of the context. Context must be understood in a broad sense: words in a statement and references to other texts, as well as cultural background.
Keywords: poljščina; glotodidaktika; jezikovna kompetenca; jezikovna kultura; medkulturnost; večjezičnost